Can alpentanil or diltiazem prevent myocardial ischemia due to tracheal intubation? - (:unkn) unknown (My University, 1999)
Objective: The aim of this study is to evaluate the efficacy of alfentanil and diltiazem to attenuate the cardiovascular responses to laryngoscopy and tracheal intubation and their effects on the occurrance of myocardial ischemia in patients with coronary artery disease. Methods: Twenty eight patients ASA II-III, 40-80 years old, scheduled for elective abdominal surgery were randomly assigned into three groups. Anesthesia was induced with 0.2 mg/kg etomidate and 1.5 mg/kg succinylcholine i.v. in all patients. In group I (n = 10) 15 μg/kg alfentanil i.v. and in group II (n = 10) 0.2 mg/kg diltiazem i.v. were administered laryngoscopy. In group III (n = 8) medication was administered. Systolic, diastolic, mean arterial pressure, heart rate, rate-pressure product and ST segment changes in DII and V5 leads were recorded before and after induction at 1., 3., 5. minutes of intubation. Results: Mean arterial pressure was significantly lower in the alfentanil and diltiazem group 1 minute after intubation. There was no significant difference in heart rate between groups. Rate-pressure product was greater than 11000 in all patients of diltiazem and control groups and in 9 patients of alfentanil group. Conclusion: Although 0.2 mg/kg diltiazem and 15 μg/kg alfentanil i.v. attenuated the hypertensive response to tracheal intubation, they were found to be ineffective in decreasing the incidence of myocardial ischemia in coronary artery disease.
Keywords: Myocardial ischemia, alfentanil, diltiazem; Tracheal intubation, hemodynamic response